Optimizing The Exclusive Breastfeeding Practices in Covid 19 Pandemic : An Articles Review - Arief, Ria Qadariah; Andyarini, Esti Novi; Hidayati, Sri (International Conference on Sustainable Health Promotion, 2021)
World Health Organization recommendations for Exclusive Breastfeeding for newborns up to 6 months. Breastfeeding has been shown to protect against infectious disease and increase body immunity, among other benefits. During the pandemic, breastfeeding becomes very crucial because the pandemic limits exclusive breastfeeding with mothers giving birth in health care facilities and other health problems that cause mothers to not be optimal in exclusive breastfeeding. We conducted exclusive breastfeeding in Pandemic Covid19. We analysed nine articles consisting of six studies considering exclusive breastfeeding for non-infected mothers and three studies presenting mothers with covid19. To optimize exclusive breastfeeding during the pandemic, promote the benefits of breastfeeding in the first-day life of newborns needed and safety giving exclusive breastfeeding practice for mothers with COVID-19 while maintaining health protocols